Overview of Problems and Solutions in the Design of Intrinsically Safe Apparatuses - Sławomir Chmielarz; Tomasz Molenda; Wojciech Korski; Krzysztof Oset; Waldemar Sobierajski (Elektronika ir Elektrotechnika, 2023)
The article presents selected basic problems occurring in the design of intrinsically safe apparatuses, solutions to some of them, and points out mistakes made during their design. The article addresses selected issues related to the design of intrinsically safe apparatuses and systems and includes a systematisation of the news and conclusions. The article also presents several project solutions for hazardous areas.